Ancient Bodies: Archaeological Perspectives on Mesoamerican Figurines, Los Angeles County Museum of Art (LACMA), July 1, 2017–February 4, 2018, Los Angeles County Museum of Art (Les Carnets de l’ACoSt)
Ancient Bodies: Archaeological Perspectives on Mesoamerican Figurines was on view at the Los Angeles County Museum of Art (LACMA) from July 1, 2017 to February 4, 2018. This exhibition explored the central role of archaeological excavation in situating ancient art and artifacts within a cultural framework.